2014
DOI: 10.1002/stem.1792
|View full text |Cite
|
Sign up to set email alerts
|

Brief Reports: A Distinct DNA Methylation Signature Defines Breast Cancer Stem Cells and Predicts Cancer Outcome

Abstract: Self-renewal and differentiation are two epigenetic programs that regulate stem cells fate. Dysregulation of these two programs leads to the development of cancer stem cells (CSCs). Recent evidence suggests that CSCs are relatively resistant to conventional therapies and responsible for metastasis formation. Deciphering these processes will help understand oncogenesis and allow the development of new targeted therapies. Here, we have used a whole genome promoter microarray to establish the DNA methylation port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…The increased expression of pluripotent genes coincides with their promoter demethylation, which suggests that demethylation of promoter DNA may be important in the epigenetic reprogramming of somatic cell nuclei [61]. Recently, El Helou et al [62] observed hypomethylation of breast CSCs in 68 differentially methylated regions compared with non-breast CSC populations, which worsen clinical outcomes.…”
Section: Linking Emt To Csc Properties and Their Epigenetic Regulationmentioning
confidence: 99%
“…The increased expression of pluripotent genes coincides with their promoter demethylation, which suggests that demethylation of promoter DNA may be important in the epigenetic reprogramming of somatic cell nuclei [61]. Recently, El Helou et al [62] observed hypomethylation of breast CSCs in 68 differentially methylated regions compared with non-breast CSC populations, which worsen clinical outcomes.…”
Section: Linking Emt To Csc Properties and Their Epigenetic Regulationmentioning
confidence: 99%
“…Moreover, promoter demethylation of achaete scute‐like 2 ( Ascl2 ), an essential transcription factor in maintaining ISC identity, results in the aberrant upregulation of ASCL2 in gastric cancer . In breast cancer stem cells (bCSCs), a whole‐genome promoter microarray analysis shows that 68 DMRs are more hypomethylated in bCSCs than in non‐bCSCs . These DMRs are significantly enriched in genes coding for transcription growth factor (TGF)‐β signalling‐related proteins, and interestingly, the hypomethylation of DMRs correlates to an overexpression of TGF‐β signalling genes in a series of 109 breast tumours, which implies that DNA methylation patterns affect tumour malignancy by regulating the transcription of genes relevant to bCSC multipotency and differentiation .…”
Section: Adult Stem Cellsmentioning
confidence: 99%
“…In breast cancer stem cells (bCSCs), a whole‐genome promoter microarray analysis shows that 68 DMRs are more hypomethylated in bCSCs than in non‐bCSCs . These DMRs are significantly enriched in genes coding for transcription growth factor (TGF)‐β signalling‐related proteins, and interestingly, the hypomethylation of DMRs correlates to an overexpression of TGF‐β signalling genes in a series of 109 breast tumours, which implies that DNA methylation patterns affect tumour malignancy by regulating the transcription of genes relevant to bCSC multipotency and differentiation . In a recent study, MSCs were reprogrammed to iPSCs and then redifferentiated into MSCs again .…”
Section: Adult Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study used whole genome promoter microarray to compare the DNA methylation portraits of human BCSCs versus non-BCSCs, and showed a distinct DNA methylation landscape in BCSCs as a key epigenetic mediator of their differentiation (20). Epigenetic silencing of the tumor suppressor breast cancer 1 (BRCA1) gene due to CpG island hypermethylation in breast cancer which contained expanded luminal progenitor cells was reported in a recent study (21).…”
mentioning
confidence: 94%